Systematic comparison of the male reproductive tract in fetal and adult Wistar rats exposed to DBP and DINP in utero during the masculinisation programming window. (15th December 2020) - van den Driesche, Sander; Shoker, Serena; Inglis, Fiona; Palermo, Christine; Langsch, Angelika; Otter, Rainer
Highlights: DINP exposure in the MPW (e15.5–18.5) does not result in effects known for DBP. DINP exposure in the MPW has no effect ADG on e21.5. Leydig cell aggregates on e17.5 and e21.5 were not increased. DINP exposure in the MPW does not induce focal testicular dysgenesis. Abstract: This study investigates possible effects of in utero exposure of rats to a low dose (125 mg/kg bw/day) and a high dose (750 mg/kg bw/day) of Diisononyl phthalate (DINP) during the masculinisation programming window (MPW) which is embryonic days 15.5–18.5 (e15.5 - e18.5). Dibutyl phthalate (DBP) was used at a high dose level (750 mg/kg bw/day) as an established positive control substance for anti-androgenic effects on the developing male reproductive tract. We focussed on the MPW and measured a multitude of biological endpoints at various life stages and applied state of the art histopathology staining techniques to refine the characterization of potential changes to the testis, beyond what is currently available with DINP. If DINP can mediate testicular dysgenesis (TDS) disorders, this exposure window would be sufficient to induce androgen impacts and alter male reproductive tract development as shown earlier in this validated experimental model with DBP. Overall, the results of this systematic comparison provide convincing evidence on the differences between the effects occurring with DBP and DINP. In contrast to what was seen with DBP, DINP did not cause cryptorchidism or hypospadias, had no effect on anogenital distance/anogenital index (AGD/AGi) and Leydig cell aggregates on e17.5 and e21.5 did not increase. With DINP no reduction of intratesticular testosterone, no effects on sperm motility and sperm count and no effect on adult testosterone or luteinizing hormone (LH) levels were seen. Our results demonstrate that DINP does not cause the adverse reproductive effects known to occur with DBP, a well-established endocrine disruptor.